Atypical carcinoid of thymus in a 39-year-old-man: A case report - García-Floriano, Lesli Alexandra (2021)
The atypical carcinoid (AC) of thymus is the most aggressive and uncommon neoplasm in the anterior mediastinum, that belongs to the neuroendocrine primary tumors of thymus. Most patients are asymptomatic and according to the disease extension they may present with cough, dyspnea, chest pain, and superior cava vein syndrome. This non-specific clinical presentation reduces the likelihood for making an early diagnosis; and this, together with disease stage and lack of surgical resection reduces the survival rate. The aim of this paper is to describe the clinical presentation in a 39-year old male with thymus carcinoid whose diagnosis was based on histopathological studies (carcinoid morphology, 0-1/2 mitoses/mm2 ), necrosis, Ki67, 12%), and immunophenotypic tumor markers [CD56(+), Pankeratin (+), Synaptophysin (+), and TTF-1 (-)].